(untitled) (ACTA MEDICA PERUANA, 2024)
"HOE 36 984 in the treatment of depressive patients". Twenty three patients with different depressive backgrounds were treated with a maleate acid of 8-amino-2 methyl-4 phenyl-1,2,3,4 tetrhydrosochinoline (Nomifensin) in the form of an open study to check the efficiency and tolerance. The psycho-drug showed an intense thymoleptical effect with an uninhibiting thymeretical component, chareacterised by the commencement of its effect within the first five day of treatment. Two patients with involuntary melancholia, four manic depressives (depressive type), one psycho-depressive and sixteen neurotic depressive cases were treated. There were only two cases of therapeutic failure, the psycho-drug showing very few side effects during the study.